2000
DOI: 10.1182/blood.v95.3.815.003k30_815_819
|View full text |Cite
|
Sign up to set email alerts
|

Molecular quantitation of minimal residual disease in acute myeloid leukemia with t(8;21) can identify patients in durable remission and predict clinical relapse

Abstract: One of the most common translocations in acute myeloid leukemia (AML) is the t(8;21), which produces the fusion gene AML1-MTG8. We have developed a sensitive competitive reverse transcriptase-polymerase chain reaction (RT-PCR) assay forAML1-MTG8 transcripts, coupled with a competitive RT-PCR for the ABL transcript as a control to accurately estimate the level of amplifiable RNA. We have shown that AML1-MTG8 andABL transcripts have equal degradation rates. Thus, this method is useful for multicenter studies. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(39 citation statements)
references
References 13 publications
4
34
0
Order By: Relevance
“…None of these children relapsed, but the median follow-up was only 5´5 years. These MRD levels are not very different from those obtained for the whole group of patients in most clinical trials including ours (Brisco et al, 1994;Cave  et al, 1998;Coustan-Smith et al, 1998;van Dongen et al, 1998). MRD level is believed to reflect the in vivo sensitivity of leukaemia blasts to chemotherapy.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…None of these children relapsed, but the median follow-up was only 5´5 years. These MRD levels are not very different from those obtained for the whole group of patients in most clinical trials including ours (Brisco et al, 1994;Cave  et al, 1998;Coustan-Smith et al, 1998;van Dongen et al, 1998). MRD level is believed to reflect the in vivo sensitivity of leukaemia blasts to chemotherapy.…”
Section: Discussionsupporting
confidence: 44%
“…MRD studies that enabled the clinically relevant thresholds of residual blasts to be determined relied on the use of TcR or IgH rearrangements, which are DNA markers present at a rate of one copy per cell (Cave  et al, 1998;van Dongen et al, 1998). The copy number of a DNA marker can easily be related to either the number of cells or the amount of DNA studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early studies showed that these transcripts persist for more than 5 years of remission after the completion of treatment (Nucifora et al, 1993), a finding that could be explained by the expression of AML1-ETO transcripts in normal monocytes, B cells and haematopoietic colony forming cells (Miyamoto et al, 2000). Despite the lack of a strict association between AML1-ETO transcripts and AML cells, careful quantification of these transcripts can help to monitor MRD (Morschhauser et al, 2000;Tobal et al, 2000). MRD studies have also been done in patients with AML and other cytogenetic abnormalities, such as inv (16).…”
Section: Mrd Studies In Genetic Subgroups Of Amlmentioning
confidence: 99%